Advances in Blue Exciplex–Based Organic Light-Emitting Materials and Devices - Li, Jie; Li, Zhi; Liu, Hui; Gong, Heqi; Zhang, Jincheng; Guo, Qiang (Frontiers in Chemistry, 2022)
Exciplexes possessing thermally activated delayed fluorescence (TADF) characteristics have received much attention in the fields of organic light-emitting materials and devices over the past decade. Generally, an exciplex is a physical mixture between a donor (D) with hole transport properties and an acceptor (A) with electron transport characteristics, and the energy difference between the lowest excited singlet state and the lowest excited triplet state is usually fairly small by means of the long-range charge transfer process from D to A. In the processes of photoluminescence and electroluminescence, triplet excitons can be converted to be singlet excitons through reverse intersystem crossing, and then radiate photons to achieve TADF. As a consequence, triplet excitons can be effectively harvested and the exciton utilization can be significantly enhanced. Up to now, a large number of exciplexes have been developed and applied to organic light-emitting devices. Thereinto, most of them showed green or red emission, while blue exciplexes are relatively few due to the spectrum characteristics of the large red-shift and broadened emission. In this paper, the latest progress of blue exciplex-based organic light-emitting materials and devices is briefly reviewed, and the future research is prospected.